A V-model approach for business process requirements elicitation in cloud design - Ferreira, Nuno (2014)
The benefits of cloud computing approaches are well known but designing logical architectures for that context can be difficult. When there are insufficient inputs for a typical (product) approach to requirements elicitation, a process-level perspective is an alternative way for achieving the intended logical design. We present a V-Model based approach to derive logical architectural models to execute in the different cloud layers from a process-level perspective, instead of the traditional product-level perspective. This V-Model approach encompasses the initial definition of the project goals and the process-level perspective of the systems intended logical architecture. The approach application results in the creation of a validated process-level structure and behavior architectural models that create a context for eliciting requirements for a cloud product. Throughout this process, we assess our decisions based on the ARID method to identify process vulnerabilities and evaluate the quality of the derived logical architecture. We introduce a case study where our approach was applied and the resulting logical architectural model is presented.